Effect of microgravity on proliferation and differentiation of embryonic stem cells in an automated culturing system during the TZ‐1 space mission. (12th July 2018) - Lei, Xiaohua; Cao, Yujing; Zhang, Ying; Qian, Jingjing; Zhao, Qian; Liu, Fangwu; Zhang, Tao; Zhou, Jiaxi; Gu, Ying; Xia, Guoliang; Duan, Enkui
Abstract: Objective: Despite a great number of studies analysing the effects of microgravity on stem cell proliferation and differentiation, few of them have focused on real‐time imaging estimates in space. Herein, we utilized the TZ‐1 cargo spacecraft, automatic cell culture equipment and live cell imaging techniques to examine the effects of real microgravity on the proliferation and differentiation of mouse embryonic stem cells (mESCs). Materials and methods: Oct4‐GFP, Brachyury‐GFP mESC and Oct4‐GFP mESC‐derived EBs were used as experimental samples in the TZ‐1 spaceflight mission. These samples were seeded into chambers, cultured in an automatic cell culture device and were transported into space during the TZ‐1 mission. Over 15 days of spaceflight, bright field and fluorescent images of cell growth were taken in micrography, and the medium was changed every day. Real‐time image data were transferred to the ground for analysis. Results: Space microgravity maintains stemness and long‐term survival of mESCs, promising 3D aggregate formation. Although microgravity did not significantly prevent the migration of EBs on the ECM substrate, it did prevent terminal differentiation of cells. Conclusions: This study demonstrates that space microgravity might play a potential role in supporting 3D cell growth and maintenance of stemness in embryonic stem cells, while it may negatively affect terminal differentiation.